The legal status of the parliamentary opposition in Ukraine and the Republic of Poland: а comparative legal analysis - Голембіовскі, Марцін; Пивовар, Майя; Golebiowski, Marcin; Pyvovar, Maya (Видавництво Львівської політехніки, 2021)
Механізми взаємодії державної влади та опозиції у європейських державах пройшли свій шлях становлення та розвитку. За цим критерієм держави Європи можна поділити на сталі демократії з багатолітніми традиціями та молоді демократії, становлення яких відбулося на межі 80-90-х років ХХ століття. До першої групи можна віднести Францію, Іспанію, Португалію, Великобританію, країни Бенілюксу та Скандинавські держави. До другої – держави східної Європи: Польщу, Словаччину, Румунію, Болгарію, Угорщину, держави Балтії, Чехію. З числа країн Центрально-Східної Європи, які вступили на шлях демократизації серед яких Республіка Польща стала першою. В статті здійснено аналіз щодо правового статусу опозиції в Україні та Республіки Польща. Авторами статті також було досліджено особливості законодавчого регулювання опозиції у Федеративній Республіці Німеччини в контексті досвіду для цих держав. Зосереджено увагу на тому, що правове регулювання механізмів взаємодії державної влади та опозиції відбувається переважно на рівні Регламентів парламентів, в яких врегульовується статус меншості. Встановлено, що в Україні та в Республіці Польща відсутнє законодавче регулювання статусу опозиції та опозиційної діяльності на рівні спеціально прийнятого закону, проте опозиція отримує державну підтримку з боку офіційної державної влади. Доведено, що належним чином інституціолізована опозиція з чітким правовим статусом та належними конституційними та законодавчими гарантіями діяльності сприятиме впровадженню нових якісних відносин у взаємодії з органами державної влади. Автори статті зосереджують увагу на тому, що в Україні та в Республіці Польща необхідно чітко закріпити на законодавчому рівні правовий статус опозиції на рівні спеціального закону. Авторами доведено, що політико-правовими механізмами взаємодії державної влади та опозиції є: 1) переговори, в тому числі за посередництвом політиків іноземних держав та представників міжнародних організацій; 2) круглі столи; 3) політичні консультації; 4) укладення політико-правових угод (договорів, меморандумів, універсалів); 5) звернення до міжнародних інституцій (Венеційська комісія, Рада Європи, ОБСЄ тощо).

The mechanisms of interaction between state power and opposition in European countries have passed through various channels of formation and development. According to this criterion, the states of Europe can be divided into stable democracies with long traditions and young democracies, the formation of which took place at the turn of the 80-90s of the twentieth century respectively. The first group includes France, Spain, Portugal, Great Britain, the Benelux countries and the Scandinavian countries. To the second – the states of Central and Eastern Europe: Poland, Slovakia, Romania, Bulgaria, Hungary, the Baltic states, and the Czech Republic. Among the countries of Central and Eastern Europe that have embarked on the path of democratization, the Republic of Poland stands out first. This article analyses the legal status of the opposition in Ukraine and the Republic of Poland. Noteworthy, the authors of this article also studied the peculiarities of the legislative regulation of the opposition in the Federal Republic of Germany in the context of the experience for these states. Special attention is focused on the fact that the legal regulation of the mechanisms of interaction between the state authorities and the opposition takes place mainly at the level of Standing Orders or Rules of Procedure, which regulate the status of a minority. It has been established that in Ukraine and the Republic of Poland there is no legislative regulation of the status of the opposition and opposition activities at the level of a specially adopted law but the opposition receives state support from the official state authorities. It has been proven that a properly institutionalized opposition with a clear legal status and appropriate constitutional and legislative guarantees will enable the introduction of quality relations in cooperation with public authorities. The authors of this article focus on the fact that in Ukraine and the Republic of Poland it is necessary to clearly enshrine at the legislative level the legal status of the opposition at the level of a special law. The authors prove that the political and legal mechanisms of interaction between the government and the opposition are: 1) negotiations, including through politicians of foreign countries and representatives of international organizations; 2) round tables; 3) political consultations; 4) conclusion of political and legal agreements (agreements, memoranda, universals); 5) appeal to international institutions (Venice Commission, Council of Europe, OSCE, etc.).
Правовий статус парламентської опозиції в Україні та Республіки Польща: порівняльно-правовий аналіз
Keywords: державна влада; парламентська опозиція; демократична трансформація; Венеціанська комісія; законодавчий статус; the state power; parliamentary opposition; democratic transformation; Venice Commission; the legal status; 340.5